Resistin in pregestational and gestational diabetic pregnancy. (16th November 2010) - Higgins, M; Russell, N; Brazil, D; McAuliffe, F
Abstract : Resistin was originally postulated to be an essential link between obesity and diabetes. The aim of the study was to investigate resistin in diabetic pregnancy. Prospective cohort study where maternal and cord samples were obtained from women with T1DM (type 1 diabetes), T2DM (type 2 diabetes), GDM (gestational diabetes) and non-diabetic controls. Clinical data were obtained. Resistin was measured by enzyme linked immunoassay (Human Resistin Enzyme Immunoassay, BioVendor Laboratorní Medicína a.s, Brno, Czech Republic). 12 non-diabetic controls, 20 women with T1DM, 14 women with T2DM and 14 women with GDM consented to the study. Matched cord samples were collected after delivery. There was a rise in maternal resistin concentration from the first to the third trimester. Maternal resistin was statistically significantly lower in T1DM and GDM compared to both non-diabetic and T2DM and this difference held in cord samples. There was no difference between non-diabetic and T2DM maternal or cord resistin concentrations. There was no significant correlation between maternal resistin and cord resistin, maternal body mass index, infant birth weight. There was no correlation between maternal resistin and maternal glycaemia (HbA1c). There was no correlation between cord resistin concentration and birth weight or maternal glycaemia. This is the first study investigating resistin in T1DM, T2DM and GDM maternal and cord blood. Resistin is significantly reduced in T1DM and GDM pregnancies compared to non-diabetic controls and to T2DM. The reduction in resistin in T1DM pregnancy may be protective as resistin also has a pro-inflammatory role.